A data analytics approach to online tourists' reviews evaluation - Christodoulou, Evripides; Gregoriades, Andreas; Papapanayides, Savvas (My University, 2020)
This paper utilizes online data of tourists' reviews from TripAdvisor to identify patterns with regards to sentiment and topics discussed by tourists that visit Cyprus, along with the investigation of the effect of tourist culture and purchasing power on reviews' polarity, using logistic regression. The analysis uses natural language processing using the LDA technique and Naïve Bayes sentiment analysis. For the data collection, custom-made python scripts were used. Ordinal logistic regression is used to identify differences among the types of tourists visiting Cyprus, in accordance to culture and purchasing power.
Keywords: Ordinal Logistic Regression; Sentiment Analysis; Topic Analysis; Tourists' Reviews